(untitled) (Geography and Tourism, 2020)
Urban space subject to constant transformation as a result of socio-economic and functional development becomes an arena for interaction and interpenetration of different elements of the urban area. In consequence, a public space with specific physiognomic features is created, reflecting the history, activities of the inhabitants, the policy of the city authorities, as well as the values of the existing natural environment. This study aims to characterize the topology of space in selected urban areas (greenspaces, bluespaces and multifamily residential areas). The subject matter is illustrated with the example of the city of Bydgoszcz, where both green and blue spaces are very visible in the landscape of the city and play an important role in its shaping. Based on their analyses of statistical and cartographic data paired with examination of planning documents, the authors propose a typology of selected elements pertaining to the city’s landscape.